Effect of Germination and Malting on the Physicochemical Properties of Maize, Finger Millet and Sorghum, and Evaluation of Quality of their Beverages - Adeleye, Ademiku O.; Ajewole, Daniel S.; Ojo, Ayobami; Oluwafemi, Temitope N.; Enujiugha, Victor N. (Journal of Agriculture, Food Technology and Sustainability, 2025)
Effect of germination and malting on the physicochemical properties of maize, millet and sorghum was investigated. The cereal grains were separately soaked in water for 18 hours, drained and germinated for 24, 48 and 72 hours, respectively. They were then dried in an air oven for 8 hours daily for 5 days at temperature of 40-50 oC. The dried samples were milled into fine flours, and then used in formulating beverages following standard methods. Proximate composition, minerals, functional properties and anti-nutritional factors were determined on the flours; while pH, total soluble solids, colour, specific gravity and titratable acidity were determined on the beverage samples. Germination led to increased nutrient contents. Malted millet gave the highest ash content of 21.8% (72 hours). Malted sorghum gave the highest fat content of 16.45% (72 hours) while the least value was recorded for malted maize 7.18% (48 hours). Malted millet gave the highest protein content of 27.33% (72 hours) while the least value for malted sorghum was 11.77% (48 hours). The anti-nutritional factors of germinated samples decreased significantly (p<0.05) compared to the control samples. The mineral contents of malted samples increased significantly (p<0.05) compared to the control. Calcium recorded highest value (13.68 mg/100g) in malted sorghum (24 hours) and lowest value (5.00 mg/100eg) in malted millet (72 hours). The beverages produced were also evaluated for microbial and sensory qualities. The beverage sample A0 (Equal weight mixture of maize, millet and sorghum flour cooked of 24 hours germination at Brix level 20) had the highest total viable count of 3.0×102 while sample C0 (Equal weight mixture (maize, millet and sorghum flour cooked of 72 hours germination at Brix level 20) had the least microbial count of 1.0×102. Germination increased the sensory acceptability of the samples. The total soluble solids had the highest value in A0 (88.13 g) and least value in A5 (Equal weight mixture of maize, millet and sorghum flour cooked of 24 hours germination at Brix level 25) (80.00 g). The pH recorded highest value in A0 (4.91) and least value in C3 (Equal weight mixture of maize, millet and sorghum flour cooked of 72 hours germination at Brix level 20) (4.13). Germination and malting generally raised the nutritional status of the cereal grains and the resultant beverages.